Hypophosphatemia in Patients With Multiple Myeloma - Cancarevic, Ivan; Ilyas, Usman; Nassar, Mahmoud (Curēus (Palo Alto, CA), 2023)
Hypophosphatemia is among the most common electrolyte abnormalities, especially among patients with underlying malignancies, and is frequently associated with adverse prognoses. Phosphorus levels are regulated through a number of mechanisms, including parathyroid hormone (PTH), fibroblast growth factor-23 (FGF-23), vitamin D, and other electrolyte levels themselves. Clinically, the findings are nonspecific, and the diagnosis is frequently delayed. This article is a narrative literature review. The PubMed database was searched for relevant articles pertaining to hypophosphatemia causes and consequences in patients suffering from multiple myeloma. We found a variety of causes of hypophosphatemia in patients with multiple myeloma. Tumor-induced osteopenia, although more common among patients with small squamous cell carcinomas, can occur with multiple myeloma as well. Additionally, both light chains themselves and medications can trigger Fanconi syndrome, which leads to phosphorus wasting by the kidney. Bisphosphonates, in addition to being a possible cause of Fanconi syndrome, lead to a decrease in calcium levels, which then stimulates parathyroid hormone (PTH) release, predisposing the patient to significant hypophosphatemia. Additionally, many of the more modern medications used to manage multiple myeloma have been associated with hypophosphatemia. A better understanding of those mechanisms may give clinicians a clearer idea of which patients may need more frequent screening as well as what the potential triggers in the individual patient may be.